Lon Po Po : A Red riding hood story from china - Young, Ed. (New York : Scholastic, 1989)
Three sisters staying home alone are endangered by a hungry wolf who is disguised as their grandmother.
Keywords: China -- Folklore; Wolves -- Folklore